APPLICATION OF INNOVATIVE METHODS IN TEACHING FOREIGN LANGUAGES - Turgunova, F.M. (SCIENCE and SOCIETY, 2024)
This article discusses the significance and features of the use of modern innovative methods in the process of teaching foreign languages. Some effective methods are presented that can be used to effectively develop speaking skills in foreign languages. A detailed analysis of the method was carried out - a drama lesson in teaching foreign languages, which has many advantages in the formation and development of students’ communicative competence.
Keywords: innovative methods; competence; communication; oral speech; theatrical lesson; creativity